Project Effectiveness Improvement: A Case Study in Indonesia Aerospace Inc. - Manalu, Zulia; Lestari, Yuliani Dwi (Journal of Business and Management, 2015)
Abstract. Project management is important and powerful tool in global business because increasingly technically complex products and processes, vastly shortened time to market demand, and the need for cross-functional expertise. PT X is aircraft industry with complex product with millions of individual components and many dependencies. The project success can achieve the customer and contractor objectives of a project, and getting the job done within the constraints of time, cost and quality. The company is delayed delivery Tail boom to Airbus Helicopter. It makes customers give complaints related to the performance of company. CPM used to analyze the project planning. After decide the method for evaluate the planning project, we must clustering 455 elementary part into activities in process production Tail Boom. PERT analysis is used when the duration of activities are not known with certainty, calculated expected time using scenario base of PERT. The expected time will use in new critical path diagram for calculate total time in actual or reality at the time happen the problems of delayed delivery Tail boom. Project Crashing used for compare the project planning and actual to know the appropriate project management.Â Keywords: Project Management, Project success, Critical Path Method (CPM), Project Evaluation and Review Technique (PERT), Project Crashing.Â